Perceptions about physical activity and its associated benefits among employees : case study in 12 Multinational Companies in Pakistan - Feroze, Farrukh (2016)
This thesis focus on the perceptions of the employees working in Multinational Corporations (MNCs) in Pakistan, with regards to their physical activity and its associated benefits. Previous research has shown that physical activity is positively associated with on-job productivity and life satisfaction of the employees across the world. With no such research being carried out in Pakistan before, this thesis aims to focus on the same factors, but uses employees’ perceptions rather than employing an intervention study. Furthermore associated benefits of physical activity such as reduced healthcare cost, decrease in exposure to various heath-risks and reduced presenteeism were also addressed within the scope of this thesis. An attempt was made to use recalled levels of physical activity to check whether the benefits associated with physical activity can be observed within the target audience as well or not.